Analysis of Factors Affecting Employee Performance - Susy Yuliastanty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
The purpose of this study was to determine the effect of motivation, job satisfaction and work discipline on the performance of PT ISS Teluk Sirih cleaning service employees, either partially or simultaneously. Data collection methods consist of field research and library research. The data collection technique used in this research is to use a questionnaire, which is a data collection technique that is done by giving a set of questions to the employees of PT. ISS Teluk Sirih. The population in this study were all employees of the cleaning service PT. ISS Teluk Sirih as many as 47 people. The number of samples from the population above was drawn using the total sampling method. The results showed 1) work motivation had a significant effect on employee performance 2) job satisfaction satisfaction had a significant effect on cleaning service employee performance 3) work discipline had a significant effect on cleaning service employee performance.